To Archive or Not to Archive: The Resistant Potential of Digital Poetry - Angello, Aaron (Text Matters: A Journal of Literature, Theory and Culture, 2015)
This essay addresses the much discussed problem of archiving digital poetry. Digital media are labile, and several writers of digital poetry are incorporating the media’s ephemerality into their poetics. Rather than rehash arguments that have been taking place within the field of digital media and digital poetics for years, I turn to the field of contemporary art curation and preservation, a field in which curators and archivists are struggling with the very immediate concerns, ethical and otherwise, related to archiving works that are made from ephemeral media. One particular digital poem that has recently broken, has recently become unreadable, is Talan Memmott’s Lexia to Perplexia. Memmott composed the poem in 2000, and he incorporated the poem’s inevitable obsolescence into the text of the poem itself. He has since refused to “fix” or “update” the poem, because he contends that that would make it something other than what it was intended to be. Rather, he is choosing to let the poem die because that is what the poem is supposed to do. This essay concludes with a discussion of the political implications of acknowledging the ephemerality of digital media, the resistant potential of the poem when its ephemerality is embraced, and some ways in which archivists can preserve the memory of the poem without necessarily preserving the poem itself.